Aquaporins in oral health and disease: A narrative review - Shailja Chatterjee (SRM Journal of Research in Dental Sciences)
Introduction: Aquaporins (AQPs) are constituted by a water-channel protein family that is distributed among different tissues. Its expression has been shown to have a significant correlation with the aggressiveness of tumors as well as prognosis. Aim: The current narrative review aimed to highlight the role of AQPs in maintaining homeostasis in cellular functioning and their expressions in diseased states and other conditions. Methods: A search was performed after entering Boolean operators with words such as “AQPs” AND “Oral health.” Research papers or systematic reviews which were published in PubMed indexed or those with Medline citations and within the past 10 years were included in the study. Results: A total of forty articles were selected during the initial screening of search engines, of which 37 articles were included in the review, while three papers were excluded, of which 1 was nonpeer reviewed and two papers did not fulfill selected inclusion criteria. Discussion: AQPs are important intramembranous transportation channels that play a significant role in both physiological and pathological conditions of the orofacial complex. The present review provides an overview of the pathophysiology involving AQPs that can help scientists to design treatment therapeutics for various disease conditions.